1990
DOI: 10.1590/s0074-02761990000200014
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the distribution of anophelines in Suriname with particular reference to the malaria vector Anopheles darlingi

Abstract: A study was made on the distribution of anophelines in Suriname with special emphasis on the principal malaria vector Anopheles darlingi and on the occurrence of other possible vector species. Peridomestic human bait collections of adult mosquitoes and collections of larvae were made in many localities with a recent history of malaria transmission. Stable populations of An. darlingi were only found in the interior, south of the limit of tidal influence, due to year-round availability of breeding habitats in qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 0 publications
1
37
0
2
Order By: Relevance
“…darlingi presents a biting activity with peaks at dusk, in the middle of the night, and at dawn, but females were also caught in daytime. In Suriname, Hudson (1984) and later Rozendaal (1987Rozendaal ( , 1989 found a biting peak around midnight. On the Maroni River, these authors showed that the peak number of bites at dusk was essentially due to An.…”
Section: Parous Rates and Vci -mentioning
confidence: 97%
See 2 more Smart Citations
“…darlingi presents a biting activity with peaks at dusk, in the middle of the night, and at dawn, but females were also caught in daytime. In Suriname, Hudson (1984) and later Rozendaal (1987Rozendaal ( , 1989 found a biting peak around midnight. On the Maroni River, these authors showed that the peak number of bites at dusk was essentially due to An.…”
Section: Parous Rates and Vci -mentioning
confidence: 97%
“…In Cayodé, from May-July 2001, the contact between man and vector was about three times higher than in the other villages, suggesting that larval habitats were exceptionally productive in this locality during this period. Hudson (1984) and Rozendaal (1987) Magris et al 2007b). In our case, considering all three villages together and the rainfall reported during the period of the study, there was a significant positive correlation between HBR and rainfall (r = 0.79, p = 0.002), with a one month lag, meaning that the abundance of An.…”
Section: Parous Rates and Vci -mentioning
confidence: 99%
See 1 more Smart Citation
“…darlingi requieren de condiciones químicas y físicas estables propias de criaderos grandes, profundos y con aguas claras, que propician temperaturas entre los 20 y los 28 °C y un pH entre 6,5 y 7,3 (53). Sin embargo, factores como la deforestación para abrir espacio a la agricultura y a la actividad minera, generan criaderos totalmente expuestos al sol que pueden alcanzar temperaturas de hasta 40 °C, con efectos importantes en el desarrollo de la especie y sus características morfológicas (54,55). Estos cambios en la composición del paisaje afectan la disposición de los criaderos y determinan cambios en la temperatura y la humedad relativa ambiental, que afectan el desarrollo de las formas inmaduras y la tasa de vuelo de los adultos.…”
Section: Discussionunclassified
“…darlingi is most commonly collected in inhabited areas and is known to be an anthropophilic species, it has also been collected in uninhabited areas suggesting that this species can utilize nonhuman blood to maintain high densities in areas or at times with few or no human inhabitants (158). It has been shown in other species that having a host preference (or specializing in a particular host) can confer fitness (107; 168).…”
Section: Before and After Bed Net Applicationmentioning
confidence: 99%